(untitled) (Bangladesh Journal of Livestock Research, 2021)
This research was conducted to study the types of lactic acid bacteria (LAB) present in selected yogurts available in the local market of Bangladesh. For this purpose, nine different yogurt samples were collected (viz. MV, Mw, Pst, Psr, Bik, Bog, WF, Kw and Nab) and cultured in the selective MRS agar media for enumerating LAB colony. Out of 9 samples, colony forming LAB were found in 6 samples and the population ranged from 1.0×104 to 9.5×105 cfu/ml. Catalase negative and Gram’s positive colonies were initially identified as LAB. Then the isolates were purified by subsequent culturing in MRS broth and MRS agar media. Biochemical properties of selected colonies were evaluated by performing gas production from glucose, growth at different temperatures (10ºC, 15ºC and 45ºC), growth at different NaCl concentrations (2, 4 and 6.5% NaCl) and sugar fermentation tests (lactose, sorbitol, salicin, trehalose, melibiose, sucrose, mannitol, melezitose, maltose, galactose, glucose, arabinose, raffinose and ribose). According to the tests stated above, a total of five different species of LAB were identified from 6 samples. The isolate Lactobacillus lactis was identified in MV, PSr and Bog yogurt, while Lactobacillus bulgaricus was found in MV and Bik yogurt. The species Leuconostoc cremoris, a avor producing bacteria, was found in six yogurt samples. On the other hand, Lactobacillus acidophilus and Lactobacillus helveticus was found only in Pst and Psr samples, respectively. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 64-72